The effect of over-indebtedness stress on workplace behavior and job attitudes among office workers in Ozamiz City, Philippines: An evidence using multi-wave and experience sampling method (ESM) - Atienza, Ringgold P. (Animo Repository, 2020)
One of the cited effects of personal over-indebtedness is productivity loss in the workplace due to employee passiveness or counterproductive behavior; however, there is a lacking theoretical foundation to explain the phenomenon. Therefore, it is vital to understand the relationship between over-indebtedness and the employee’s behavior in the organization. This study applied both the cognitive appraisal theory of stress and conservation of resource theory. This study examined the relationship between the employee’s indebtedness stress and workplace behavior (i.e., work withdrawal, workplace incivility, task proficiency, organizational citizenship), considering whether an employee appraises indebtedness stress as a threat a challenge in the point of view of the cognitive appraisal theory of stress using the experience sampling method (ESM) as study 1. Alternatively, drawing on the conservation of resources theory, this study examined the relationships among employees' indebtedness stress, self-regulation depletion, and workplace attitude (i.e., job satisfaction, organizational commitment) utilizing a three-wave longitudinal survey as study 2. This study also examined the moderating role of financial cognitive biases (i.e., optimism, risk propensity) and behavioral traits (i.e., materialism, resilience). The study was conducted in Ozamiz City, Misamis Occidental, Philippines. Study 1 used multi-level SEM panel data through individual daily records among 35 office employees for ten days. Results from study 1 suggest over-indebtedness stress is unlikely appraised as a challenge but only as a threat. This means that stress resulting from over-indebtedness is a harmful type of stress that only results in resource depletion of individual and negative behavior. It also showed that optimism and resilience traits significantly moderates the effect of indebtedness stress and threat appraisal. Thus, both optimism and resilience reduce the effects of indebtedness stress. Results from study 2 support hypothesized relationships of the conceptual framework of the researcher. Results show that indebtedness stress negatively impacts job attitudes through self-regulation depletion. It also showed that both optimism and resilience reduce the effects of indebtedness stress. Overall, the researcher provides an integrative model to explain the effect of indebtedness stress on work-behavior and job attitudes among office workers. This study contributes to the literature in several important ways. First, this study has found that indebtedness stress is unlikely a source for personal growth, gain, or mastery. Second, this study has shown that indebtedness stress can result in long-term psychological distress and resource loss spiral among employees. Third, the result means that indebtedness stress can become a persistent problem when employees are not given social support. Finally, this study provides insights to help managers understand and deal with employees experiencing worklife interference problems, specifically employees having debt problems.